PENGARUH RASIO KEUANGAN TERHADAP JUMLAH BAGI HASIL SIMPANAN MUDHARABAH PADA PT BANK SYARIAH MANDIRI TAHUN 2006-2013 - Retno Oktapiani; Ida Busneti (Media Ekonomi, 2015)
Banks as institutions of trust are not only needed or beneficial for individuals and society as a whole but also play a role in the growth and economic development of a country. In addition, banks can also help facilitate transaction, production and consumption activities through their functions as institutions that carry out payment traffic. Similarly, banks also play a role in implementing monetary policy. The effectiveness of monetary policy can work well influenced by the health and stability of the banking business. This study wants to see the effect of financial ratios on the number of profit sharing of mudharabah deposits in Islamic banks by using the bank's financial ratio variables, namely Liquidity Ratio in the form of FDR and Current Ratio, Solvency Ratio (Capital) in the form of CAR, Earning Ratio (Earning) in the form of ROA and ROE, and Business Efficiency Ratios in the form of NIM and BOPO at BSM in 2006-2013. The method used is a descriptive method and hypothesis testing. Hypothesis testing method, using multiple linear regression (multiple regression). The model used will be estimated using the Ordinary Least Squares (OLS) model and the Classic Assumption Test. The results of this study are the Ratio of Liquidity, Solvability, Profitability, and Efficiency of Business significantly influence the amount of profit sharing of mudharabah savings